Targeting TMAO and its metabolic pathway for cardiovascular diseases treatment - Hoseini-Tavassol, Zahra (J Diabetes Metab Disord, 2021)
Given the prevalence of cardiovascular diseases (CVDs), as one of the most important non-communicable diseases (NCDs), the recognition of diagnostic biomarkers and potential treatment methods is very crucial. Today gut microbiota composition and its derived metabolites modification are known as one of the recent therapeutic strategies. Studies show that Trimethylamine N-oxide (TMAO) is a gut microbiota-derived metabolite that may be involved in the development of cardiovascular diseases, including ischemic disease and atherosclerosis, atrial fibrillation and arrhythmia, and heart failure. Due to existing some disagreements in this manner, future studies are needed to obtain a definitive sight of the association between this metabolite and CVDs. TMAO may be beneficial as a prognostic marker, which represents the degree of gut microbiota dysbiosis and subsequently CVD events and also different therapies methods based on TMAO and its metabolic pathways can be the target of clinical trial on cardiovascular disease and/or its prevention.